The relationship of age with the clinical phenotype in multiple sclerosis. (November 2016) - Scalfari, A; Lederer, C; Daumer, M; Nicholas, R; Ebers, GC; Muraro, PA
Background: The multiple sclerosis (MS) clinical course and relapses frequency before progression vary widely. Objective: To investigate the influence of age on the MS phenotype. Methods: Among 751 primary progressive (PP = 217) and secondary progressive (SP = 534) MS patients from the London Ontario database, we assessed the relationship of age on the relapse frequency and on the progressive phase evolution, and the impact of relapses on the age at onset of progression. Results: Age at onset did not influence the early attacks frequency, but patients younger at onset had larger number of total attacks before progression (age = 27.4, 31.0 and 32.8 mean years; ⩾4, 2–3 and 1 relapses, respectively) and longer latency to SP. Although frequent early relapses predicted younger age at SP onset, patients with no attacks (primary progressive multiple sclerosis (PPMS)), or 1, 2–3 and ⩾4 relapses during the relapsing-remitting phase started progressing at similar age (38.6, 41.3, 41.4 and 39.2 mean years, respectively). The age at onset of progressive phase did not affect its evolution. Conclusions: Age strongly influences the phenotype before progression. Relapsing-remitting patients younger at onset are more likely to display a predominantly inflammatory course, yet relapses number does not affect the age at onset of progression.